Analyze The Contribution of Bangladesh Krhisi Bank in The Development of Agricultural Sector in Tangail District, Bangladesh - Saha, Subrata; Abbasi, Al Amin Al; Rahman, Abida (IJRDO - Journal of Business Management, 2017)
The economy of Bangladesh highly depends on Agriculture. The significant portion of GDP comes from agricultural sector. In this paper, we have explored how Bangladesh Krishi Bank (BKB) contributes on agricultural sector of Tangail district (south zone). We have explained the trend of loan disburse, loan recovery, deposit and profit of nine branches of BKB in tangail south zone from 2011-2015. This study discuss the pattern of loan disburse and recovery on specific three sector named crops, fisheries and livestock. The finding shows that approximately 70% of total loan are given to crops sector, 20% on fisheries and remaining 10% on livestock sector and the amount of loan distributed during the period 2011-2015.We have used balanced panel data and fixed effect model for regression to find out the relationship among loan recovery and loan disburse, deposit and profit. The findings tell us loan disburse, deposit, profit have a relation with loan recovery but loan recovery has statistically significant (p<.05) relationship with loan disburse and deposit. These studies suggest that agricultural credit helps to enhance the development of agricultural activities in Tangail district. As a result overall production of agricultural products increased which helps to meet up the local and national demand.